Increased PD-1+Foxp3+ γδ T cells associate with poor overall survival for patients with acute myeloid leukemia - Zheng, Jiamian; Qiu, Dan; Jiang, Xuan; Zhao, Yun; Zhao, Haotian; Wu, Xiaofang; Chen, Jie; Lai, Jing; Zhang, Wenbin; Li, Xutong; Li, Yangqiu; Wu, Xiuli; et al. (Frontiers in Oncology, 2022)
Problems γδ T cells are essential for anti-leukemia function in immunotherapy, however, γδ T cells have different functional subsets, including regulatory cell subsets expressing the Foxp3. Whether they are correlated with immune-checkpoint mediated T cell immune dysfunction remains unknown in patients with acute myeloid leukemia (AML). Methods In this study, we used RNA-seq data from 167 patients in TCGA dataset to analyze the correlation between PD-1 and FOXP3 genes and these two genes’ association with the prognosis of AML patients. The expression proportion of Foxp3+/PD-1+ cells in γδ T cells and two subgroups Vδ1 and Vδ2 T cells were performed by flow cytometry. The expression level of FOXP3 and PD-1 genes in γδ T cells were sorted from peripheral blood by MACS magnetic cell sorting technique were analyzed by quantitative real-time PCR. Results We found that PD-1 gene was positively correlated with FOXP3 gene and highly co-expressed PD-1 and FOXP3 genes were associated with poor overall survival (OS) from TCGA database. Then, we detected a skewed distribution of γδ T cells with increased Vδ1 and decreased Vδ2 T cell subsets in AML. Moreover, significantly higher percentages of PD-1+ γδ, Foxp3+ γδ, and PD-1+Foxp3+ γδ T cells were detected in de novo AML patients compared with healthy individuals. More importantly, AML patients containing higher PD-1+Foxp3+ γδ T cells had lower OS, which might be a potential therapeutic target for leukemia immunotherapy. Conclusion A significant increase in the PD-1+Foxp3+ γδ T cell subset in AML was associated with poor clinical outcome, which provides predictive value for the study of AML patients.